Identification of the Alternative Splicing of the UL49 Locus of Human Cytomegalovirus. (19th March 2015) - Yang, Guang; Li, Wei; Liao, Wenzhen; Zhang, Xin; Zou, Yi; Dai, Jianfeng; Li, Yueqin; Jing, Chunxia; Zhou, Tianhong
Abstract : The UL49 ORF of human cytomegalovirus (HCMV) is essential for viral replication; conserved among all herpes viruses; however, the function is unclear. Once the UL49 ORF was precisely deleted from the start to stop codon, the mutant did not yield infectious progeny. In this study, we find out many alternatively processed ESTs in UL49 locus in HCMV-infected cells, in which there are two novel transcription termination sites in UL49 locus. Most of these ESTs are rare transcripts that contain directed repeat sequences in the intron splicing regions. There is a typical GU-AG intron splicing site in UL49Y transcripts. The 1847 bp UL49Y cDNA spans an ORF from 335 to 1618 and encodes a putative protein of 427 amino acids with a predicted molecular mass of 47.1 kDa. All the new EST sequences and UL49Y cDNA sequence have been deposited in the GenBank database (GenBank Accession nos. GW314860-GW314900 and GU376796). This study provides us with very important clues for revealing the importance of the UL49 locus alternative splicing.